2023
DOI: 10.1108/jmtm-03-2023-0085
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of knowledge management process toward minimizing technical risks under green implementation network: a direct and configurational approach

Abstract: PurposeThe knowledge management (KM) sharing process plays an essential role in manufacturing under Green Implementation Network (GIN). This study aims to analyze the KM process of adopting a GIN to determine the relative importance of technical risk minimization. The proposed conceptual model was tested by considering two interrelated concepts (GIN and KM process).Design/methodology/approachPrimary data from manufacturing companies in Henan province, China, were collected through 276 questionnaires. PLS-SEM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 93 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…It is evident that DC is instrumental in implementing a manufacturing firm's policies and strategies, enabling them to adapt to volatile business environments and fostering innovation [22,36,129]. The sensing, seizing, and reconfiguring activities enabled by dynamic capabilities can effectively harness the potential of social capital to enhance PGI in manufacturing enterprises, illustrating that social capital can drive PGI primarily through DC.…”
Section: Plos Onementioning
confidence: 99%
“…It is evident that DC is instrumental in implementing a manufacturing firm's policies and strategies, enabling them to adapt to volatile business environments and fostering innovation [22,36,129]. The sensing, seizing, and reconfiguring activities enabled by dynamic capabilities can effectively harness the potential of social capital to enhance PGI in manufacturing enterprises, illustrating that social capital can drive PGI primarily through DC.…”
Section: Plos Onementioning
confidence: 99%
“…The consequence of the study indicated that knowledge sharing minimized the manufacturing risk under GT implementation. Moreover, the recent study analyzed technical risk based on KM and GT implementation (Alam et al ., 2023c). The result demonstrated that technical risk was minimized based on KM and GT implementation.…”
Section: Theoretical Underpinning and Hypothesis Developmentmentioning
confidence: 99%